2015
DOI: 10.1177/230949901502300305
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Tranexamic Acid Wash during Bilateral Total Knee Arthroplasty

Abstract: Purpose.To compare the outcome after simultaneous bilateral total knee arthroplasty (TKA) with or without an intra-articular tranexamic acid (TXA) wash in terms of blood loss, haemoglobin change, and transfusion requirement. Methods. 35 women and 10 men (mean age, 67.5 years) who underwent primary simultaneous bilateral TKA by a single senior surgeon were compared with 45 matched controls. In the TXA group, 1500 mg of TXA diluted in 100 ml of 0.9% sodium chloride was administered as a wash after cementing of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…To date, only a few studies have demonstrated the effectiveness of TXA in simultaneous, bilateral TKA (Table 1) [1, 3, 4, 6, 9-11, 13, 21, 22, 26], and only one recent study [4] directly compared different dosing regimens of intravenous TXA in this cohort. Goyal et al [4] analyzed the difference between a single dose of TXA and three doses of TXA and found no differences in the mean drop in hemoglobin, mean drop in hematocrit, and need for blood transfusions between groups.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have demonstrated the effectiveness of TXA in simultaneous, bilateral TKA (Table 1) [1, 3, 4, 6, 9-11, 13, 21, 22, 26], and only one recent study [4] directly compared different dosing regimens of intravenous TXA in this cohort. Goyal et al [4] analyzed the difference between a single dose of TXA and three doses of TXA and found no differences in the mean drop in hemoglobin, mean drop in hematocrit, and need for blood transfusions between groups.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 383 records were identified of which finally 69 were found appropriate for inclusion in the present meta‐analysis (fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of intravenous TXA in simultaneous bilateral total knee arthroplasty was reported in previous retrospective comparative studies 20 - 22 and randomized controlled trials 15 , 23 . The effectiveness of intra-articular TXA was also reported in a retrospective comparative study 24 . Several randomized controlled trials compared the effectiveness of intravenous TXA with that of intra-articular TXA 25 , 26 .…”
Section: Discussionmentioning
confidence: 96%